Chromatin accessibility derived from cfDNA serves as a novel classification biomarker of glioma - Wu, Qiuyue; Wu, Jian; Wang, Fan; Wang, Qiang; Dai, Wei; Yang, Yang; Zhang, Chuanyue; Han, Ying; Chen, Min; Pan, Hao; Luo, Lan; Xia, Xinyi (Frontiers in Oncology, 2025)
IntroductionGliomas can be classified by their molecular characteristics, which are also closely associated with clinical outcomes. Cell-free DNA (cfDNA)-based liquid biopsy in gliomas is challenging because of the limited amount of tumor-derived cfDNA present in body fluids.MethodsIn this study, we identified the open chromatin states of gliomas using cfDNA and demonstrated the potential of this technique for glioma detection. The chromatin accessibility of gliomas was investigated using tumor tissues donated by four donors. cfDNA derived from paired cerebrospinal fluid (CSF) and plasma samples was also sequenced.ResultsA total of 72 accessible chromatin regions in the tumor tissues were identified as open chromatin regions using CSF cfDNA. Furthermore, 16 open chromatin regions with significant differences in glioma grade were found using cfDNA extracted from plasma. A glioma grade classifier was constructed with 16 plasma cfDNA-derived accessible chromatin features, which could accurately differentiate low-grade from high-grade samples in the training dataset Area Under Curve ((AUC) = 0.814). However, lower accuracy was obtained on the testing dataset (AUC = 0.736). The diversity of transcription factor binding sites among glioma patients was also illustrated using cfDNA.DiscussionIn conclusion, our study defines novel chromatin-accessibility-based biomarkers and illustrates their potential application in glioma liquid biopsy.